2015
DOI: 10.1021/ic502807d
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Ligand Effects and Probing the Inner-Workings of Bond Activation Steps: Generation of Ruthenium Complexes with Tailor-Made Properties

Abstract: Activating chemical bonds through external triggers and understanding the underlying mechanism are at the heart of developing molecules with catalytic and switchable functions. Thermal, photochemical, and electrochemical bond activation pathways are useful for many chemical reactions. In this Article, a series of Ru(II) complexes containing a bidentate and a tripodal ligand were synthesized. Starting from all-pyridine complex 1(2+), the pyridines were stepwise substituted with "click" triazoles (2(2+)-7(2+)). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 83 publications
(21 reference statements)
3
26
0
Order By: Relevance
“…These energies can be determined or inferred spectroscopically, electrochemically and computationally and as [Ru(N^N) 3 ] 2+ complexes invariably have a highest occupied molecular orbital of predominantly metallic 4d character, and hence effectively the same ground state, these excited state energies can be readily compared). Work in our laboratory, [26][27][28] and those of others, [29][30][31][32] has shown that complexes containing 1,2,3-triazole rings that lack such steric promotion can also lead to photochemical reactivity, possibly through destabilisation of the 3 MLCT state with respect to the 3 MC state when compared to those states of the archetypal complex [Ru(bpy) 3 ] 2+ . We recently reported the series of complexes [Ru(bpy) 3-n (btz) n ] 2+ (btz = 1,1'-dibenzyl-4,4'-bi-1,2,3-triazolyl, n = 1 to 3) 33 in which an increasing number of btz ligands leads to destabilisation of the 1 MLCT bands in the visible absorption spectrum, significantly so for the homoleptic complex [Ru(btz) 3 ] 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…These energies can be determined or inferred spectroscopically, electrochemically and computationally and as [Ru(N^N) 3 ] 2+ complexes invariably have a highest occupied molecular orbital of predominantly metallic 4d character, and hence effectively the same ground state, these excited state energies can be readily compared). Work in our laboratory, [26][27][28] and those of others, [29][30][31][32] has shown that complexes containing 1,2,3-triazole rings that lack such steric promotion can also lead to photochemical reactivity, possibly through destabilisation of the 3 MLCT state with respect to the 3 MC state when compared to those states of the archetypal complex [Ru(bpy) 3 ] 2+ . We recently reported the series of complexes [Ru(bpy) 3-n (btz) n ] 2+ (btz = 1,1'-dibenzyl-4,4'-bi-1,2,3-triazolyl, n = 1 to 3) 33 in which an increasing number of btz ligands leads to destabilisation of the 1 MLCT bands in the visible absorption spectrum, significantly so for the homoleptic complex [Ru(btz) 3 ] 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…For performing such reactions synthetic chemists usually use the thermal method. [6,8] On one-electron oxidation the originally Sbound DMSO ligand can dissociate and recoordinate, now Obound, to the metal center. While weakening of existing metal-ligand bonds is at the heart of all the three aforementioned methods, the ways and means in which such weakening is achieved are very different for all three methods.…”
mentioning
confidence: 99%
“…[1] Less frequently electrochemical or photochemical bond activation strategies are used for the synthesis of novel transition metal complexes as well. [6,8] However, the oxidation waves of 1 and 2 (Figure 2) are fully reversible even at very low scan rates (I pc /I pa > 0.98 for the measurements at 10 mV s À1 (Fig-[a] J. Particularly intriguing is the comparison of a thermal bond activation to the photochemical bond activation of the same bond.…”
mentioning
confidence: 99%
See 2 more Smart Citations